2010
DOI: 10.1111/j.1750-3841.2009.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Potato Starch and Water‐Vaporization Behavior of Its Paste Controlled with Amino Acid and Peptide‐Rich Food Materials

Abstract: The particular effect of 4 kinds of amino acid and peptide-rich food material (APRM) containing different charged amino acid contents on the gelatinization and retrogradation behavior of potato starch granules and on the water-vaporization behavior was analyzed by differential scanning calorimetry, rapid viscoanalysis, x-ray diffractometry, thermal gravimetry-differential thermal analysis, and pulsed NMR. APRM with a high-charged amino acid content produced unique gelatinization and retrogradation behavior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For the degree of crystallinity, RS‐Glu was the fewest, followed by RS‐Lys. Rice starch supplemented without amino acid was the most crystalline among all samples, which indicated that the short‐term retrogradation of rice starch gels were delayed by supplemented with Gly, Lys, and Glu in terms of decreasing the reconstitution of the ordered structure .…”
Section: Resultsmentioning
confidence: 93%
“…For the degree of crystallinity, RS‐Glu was the fewest, followed by RS‐Lys. Rice starch supplemented without amino acid was the most crystalline among all samples, which indicated that the short‐term retrogradation of rice starch gels were delayed by supplemented with Gly, Lys, and Glu in terms of decreasing the reconstitution of the ordered structure .…”
Section: Resultsmentioning
confidence: 93%
“…The GluNa‐mixed starch showed no substantial changes in its pasting properties compared with the untreated starch, whereas the control starch showed an obvious reduction in its peak viscosity (PV), breakdown (BD), and setback (SB) and a rise in its pasting temperature (PT) (Table 2), as described previously (Yagishita and others 2008). On the other hand, the GluNa‐compounded starch exhibited marked changes in these pasting properties, in particular, marked reductions in PV and BD depending on the amount of GluNa added during the compounding, which corresponded well to the increased gelatinization temperature and decreased swelling described previously.The reduced swelling could result in easy vaporization of external water in the swollen starch granules in starchy batter, contributing to giving a dry texture during frying in hot oil or re‐heating by microwave(Yagishita and others 2008; Sakauchi and others 2010). This unique pasting behavior with significantly reduced swelling suggests that GluNa‐compounded starch could effectively contribute to improving the sticky and pasty texture of starchy foods.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction product adjusted to pH 7.0 was applied to a DEAE-Sepharose Fast Flow column (2.8 cm inner diameter × 7.5 cm) that had been equilibrated with a 0.02 M borate buffer (pH 7.0) and eluted stepwise with 800 mL of the same buffer and then 800 mL of the same buffer containing 1.0 M NaCl. The NaCl−eluate was desalted by an electrodialyzer (Astom S3 Microacylazer, Tokyo, Japan) to give 0.15 mS/cm as previously described . The resulting desalinate was concentrated in a rotary evaporator (Shibata, Tokyo, Japan) to 300 mL and then lyophilized to recover BOS-P.…”
Section: Methodsmentioning
confidence: 99%
“…The NaCl-eluate was desalted by an electrodialyzer (Astom S3 Microacylazer, Tokyo, Japan) to give 0.15 mS/cm as previously described. 17 The resulting desalinate was concentrated in a rotary evaporator (Shibata, Tokyo, Japan) to 300 mL and then lyophilized to recover BOS-P.…”
Section: ' Materials and Methodsmentioning
confidence: 99%